The Great Reset. Restratification for lives, livelihoods, and the planet - Roth Steffen (Elsevier B.V., 2022)
In reviewing the Great Reset, an initiative launched by the World Economic Forum (WEF) in response to the global coronavirus crisis, this perspective article considers the scenario of an epochal transition from capitalism to “restorism”. To facilitate the observation of underlying trends and assumptions, a systems-theoretical framework is developed for the observation of both this Great Reset scenario and those scenarios that are by implication excluded by the WEF vision. It is thus shown that the “shared goals” advocated by the WEF would converge to a transition from a modern pluralist to a “new-normative” order stratified to the primacy of indi- vidual, institutional, and planetary health. In discussing sociological implications of this transition, a vision emerges of a new digitally enhanced medieval era where health plays the role once played by religion. In this restorist scenario of a neo-medieval world health society, the emergence of new social strata corresponding to different levels of purity, infection, or pollution would be a probable consequence. The paper concludes that idea of deliberately caused great resets and other control illusions nurtured by the WEF initiative are barely smarter than and spur what the UN Secretary-General refers to as “wild conspiracy theories”.